2020
DOI: 10.1108/jcm-12-2019-3536
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the institutional environment on green consumption in India

Abstract: Purpose This paper aims to develop an institutional framework to examine the role of governmental and social pressures on green product purchase intentions. Because of the increased focus on environmental issues in emerging markets, an examination of the institutional environment in India can provide unique insights into the drivers of green consumption. Design/methodology/approach A large-scale data collection is conducted via an online survey to test the validity of the theorized model. A survey methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 74 publications
(79 reference statements)
3
23
0
Order By: Relevance
“…In addition, NS strengthens the relationship between WG and GCPI . The result confirms that normative pressure can be classified as a strong determinant for restricting or guiding individuals’ behaviors in the context of gamified charity, which can be claimed following previous research ( Urban and Kujinga, 2017 ; Sreen and Gleim, 2020 ). By contrast, a non-significant relationship is observed between AR and GCPI , which can further lead to the gap in public understanding and framing issues.…”
Section: Discussion and Implicationsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, NS strengthens the relationship between WG and GCPI . The result confirms that normative pressure can be classified as a strong determinant for restricting or guiding individuals’ behaviors in the context of gamified charity, which can be claimed following previous research ( Urban and Kujinga, 2017 ; Sreen and Gleim, 2020 ). By contrast, a non-significant relationship is observed between AR and GCPI , which can further lead to the gap in public understanding and framing issues.…”
Section: Discussion and Implicationsupporting
confidence: 88%
“…The literature argues that NS has been adopted in several research fields, such as technology adoption ( Teo et al, 2003 ; Liang et al, 2007 ), green innovation ( Aguilera-Caracuel and Ortiz-de-Mandojana, 2013 ; Berrone et al, 2013 ), and entrepreneurial activity ( Valdez and Richardson, 2013 ). Moreover, Urban and Kujinga (2017) suggested that NS significantly influences social entrepreneurship intentions, which are further examined in green initiatives and pro-environmental concerns by Sreen and Gleim (2020) .…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Generation Y is a cohort of individuals born approximately between 1980 and 2000 (Deloitte, 2021). They tend to be brand conscious, seek status and prestige, have strong feelings about nature and are responsive to marketing campaigns that feature the benefits of products to the natural environment (Cosgrave and O'Dwyer, 2020;Sreen et al, 2021;Savelli et al, 2020;Weber, 2015).…”
Section: Eco-brand Orientation Of Millennial Consumers: a Social Cognitive -Institutional Perspectivementioning
confidence: 99%
“…Previous studies focus on millennials' attributes such as values, personalities, attitudes and preferences driven by some cognitive drivers while relegating the external environmental or contextual situations to the background (Savelli et al, 2020;Cosgrave and O'Dwyer, 2020;Mittendorf, 2018). A lacuna in the green consumer literature on studies that examine how the external institutional environment, such as the role of the government and its regulatory agencies and various social norms and expectations, impacts millennial consumer choices (Agnihotri and Bhattacharya, 2019;Sreen et al, 2021). To better understand the millennial consumers' choices, it is essential to consider their moral agency and interaction with their social and institutional contexts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation